Internal quantum efficiency in polar and semipolar (11–22) InxGa1-xN/InyGa1-yN quantum wells emitting from blue to red. (January 2018) - Ngo, Thi Huong; Chery, Nicolas; Valvin, Pierre; Courville, Aimeric; de Mierry, Philippe; Damilano, Benjamin; Ruterana, Pierre; Gil, Bernard
Abstract: In this work, we investigate the impact of the quantum confined Stark effect and of the carrier localization on the internal quantum efficiency of polarized single or multiple Inx Ga1-x N/GaN quantum well(s), and semi-polar (11–22) multiple Inx Ga1-x N/Iny Ga1-y N quantum well. We find that increasing the influence of the quantum confined Stark effect at constant indium content with increasing the well-width induces a reduction of the internal quantum efficiency onsets for a decreasing value of the photoexcitation density. Similar but no so dramatic trend is reported when increasing the indium content and thus when increasing the localization of carriers to localized fluctuations of the chemical composition of the alloy. In addition, a change of the electric field internal to active layers (quantified by using time-resolved photoluminescence spectroscopy) realized by growing samples along a semi-polar orientation leads to experimental observation of a substantial enhancement of the threshold of photoexcitation density at which onsets the reduction of the internal quantum efficiency. A correlation is found through several orders of magnitude between the photoexcitation density PT for the onset of the collapse of IQE and the values of the photoluminescence radiative decay time τrad . A scaling law is found in the investigated samples: PT ∼ τrad - n with n = 3/2 ± 0.15 which evidences that quantum confined Stark effect is the main origin for the efficiency droop in nitride light-emitting diodes based on Inx Ga1-x N active layers. Highlights: We investigate the impact of the quantum confined Stark effect and of the carrier localization on the internal quantum efficiency of polar single or multiple Inx Ga1-x N/GaN quantum well(s), and semi-polar (11–22) multiple Inx Ga1-x N/Iny Ga1-y N quantum well. We disentangle the contributions of Quantum Confined Stark effect from the one of localization of carriers that triggers the onset of the reduction of the internal quantum efficiency. We find that for enhancing the IQE, it is mandatory to reduce the amount of carriers localized by the electric field at hetero-interfaces. Therefore, semi-polar structures with high crystalline quality are potential solutions for the growth of efficient green and longer wavelengths light emitters.